Sosialisasi Strategi Menarik Minat Konsumen Untuk Membeli Produk Hasil UMKM - Dede Suleman; Sabil; Ida Zuniarti; Sri Rusiyati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2021)
This activity aims to provide knowledge about the importance of understanding consumers in this new era because in the sales process in the era and the COVID-19 pandemic, consumer behavior will definitely change. Therefore, the activity with the theme